(untitled) (Sains Humanika, 2009)
The aim of this research was to (1) identify the frequency of implementation of various dimensions of leadership style among Co–curricular Senior Assistants; (2) analyze relationships between demographic factors and the achievements of the school athletics team; (3) study the relationships between the frequency of implementation for each dimension of leadership style and the achievements of the school athletics team; (4) determine significant predictors which contribute to the achievements of the school athletics team. A total of 48 Co–curricular Senior Assistants from 48 primary schools located in Air Itam and Kelawai zones were selected as research subjects. Research instrument Leadership Scale For Sports (LSS) used to measure the frequency of implementation for leadership styles consists of five dimensions such as training and order, democratic, autocratic, social support and reward. While the achievements of the school athletics team were determined by the achievements during Penang Schools Sports Council Athletics Meet over a period of three years from 2004 to 2006. In addition, demographic factors of Co-curricular Senior Assistants included gender, marital status, experience in the field of sports, sports qualifications and experience serving as Sport Administrators. The conclusion of the research was (1) the mean frequency of implementation for all dimensions of leadership style was more than 3.00 except for autocratic dimension mean at only 1.57. The reward dimension was the dimension that was frequently practiced by Co-curricular Senior Assistants; (2) The correlation analysis showed that significant, positive and strong relationship exist between demographic factors, sports qualifications (r = 0.819) and experience in the field of sports (r = 0.704) and the achievements of the school athletics team at the level 0.05. Findings from this study showed significant, positive and strong relationships between the frequency of implementation of reward leadership style and sports achievement. The reward kind of leadership style and three other demographic factors which are experience in the field of sports, sports qualifications and experience serving as Sports Administrators proved to be strong predictors for the achievement of the school athletics team. Further discussion in this article is the implications towards professional development of sports administrators, in nurturing potential athletes.